Analisis Manajemen Perawatan Luka pada Kasus Luka Diabetik di Instalasi Gawat Darurat (IGD) Rumah Sakit Arifin Nu'mang Kabupaten Sidrap - Ungke, Damsir Eni (Window of Health : Jurnal Kesehatan, 2018)
Diabetic injury is one form of chronic complications. Diabetes mellitus is an open wound on the skin surface that can be accompanied by local tissue death. Diabetes mellitus patients at risk of 29 times the occurrence of diabetic injuries. Diabetic injury is an open wound on the skin surface caused by the presence of macroangiopathy resulting in vascular insusifiensi and neuropati. Organs most often affected by diabetes mellitus complications include the leg blood vessels. Disorders of blood vessels that often occur in diabetes that is on the legs and feet. This study aims to determine the effectiveness of wound care using modern bandage (Metcofazin) on diabetic wound healing process at Emergency Hospital (IGD) Arifin Nu'mang Hospital of Sidrap Regency, and to know the effectiveness of wound care using conventional dressing (normal saline saline NaCl 0 , 9% and gauze bandage) to diabetic wound healing process at Emergency Injury Installation (IGD) Arifin Nu'mang Hospital of Sidrap Regency. The type of research used by the researcher is qualitative research with case study approach. This research has been conducted on 21 November until December 21, 2014 at the Emergency Installation (IGD) Arifin Nu'mang Hospital, Sidrap Regency. Samples used in this study are patients with diabetic injuries at Arifin Nu'mang Hospital Sidrap District with sampling technique by puposive sampling. The results of this study indicate that the treatment of luk a using a modern bandage (metcofazine) is more effective than wound care using conventional dressing (normal saline 0.9% NaCl saline and gauze dressing) on ​​diabetic wound healing process at Arifin Nu'mang Hospital Sidrap Hospital.